Tolerância a germinação na espiga e produtividade de grãos de genótipos de trigo em duas épocas de semeadura - Jandrey, Paulo Evandro (2013)
Knowledge of the degree of seed germination in the ear is useful both for crop condition as for breeding in wheat. The results of the different tests used to identify cultivars with improved tolerance of sprouting indicate that there is possibility to keep the grains with suitable properties for industry, enabling decrease the amount of losses occurring on the wheat production areas. Accordingly, the aim of this study was to evaluate the tolerance to sprouting and grain yield in wheat grown at two sowing dates. The field experiment was conducted in the area of the Center of Research in COODETEC Palotina-PR using randomized blocks with 15 x 2 factorial arrangement with 3 replications. The first factor refers to genotypes, 3 cultivars (Mirante, CD 150 and Frontana) and 12 lineages resulting from the backcross of cultivars CD 150 with Frontana (CD 12901, CD 12902, CD 12903, CD 12904, CD 12905, CD12906 , CD 12907, CD 12908, CD12 909, CD12 910, CD12 911 and CD 12912). The second factor relates to the two sowing dates (31/03 and 05/03/2012). Plots consisted of 6 rows of 6 meters in length, 0.17 meters spacing between lines, being regarded as one boundary line on each side and 0.50 meters from each end. Evaluations of sprouting, the experiments were conducted in the laboratory, using a randomized block design in 15 x 2 factorial arrangement with 4 replications, each replication was composed of 10 spikes. In the evaluations of sprouting was evaluated for germination in two distinct metologias (immersion in water and rainfall simulator). The variable number of days to silking, plant height, thousand grain weight and number of grains per spike were the characteristics that have greater variability among genotypes, and the sowing in 03/05 was the one that led to the highest for plant height, test weight, number of spikelets per spike and number of grains per spike. The cultivar Frontana showed high resistance to germination of the grain in the ear, regardless of sowing and methodology. Genotypes CD 12901, CD 12905, CD 12907 showed tolerance to the germination of the grain in the ear when evaluated by the method of rainfall simulator in sowing on 31/03. Highest grain yield was obtained for genotypes CD 12902, CD 12905, CD 12909, CD 12910 and CD 12911 in sowing in 03/05. Already Frontana to cultivate, cultivate greater number of days to silking, the highest yield was obtained in sowing on 31/03